MOTIVASI BONUS, PAJAK, DAN UTANG DALAM TINDAKAN MANAJEMEN LABA (STUDI PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2015) - Novia Fitri Kusumawardani; R. Rosiyana dewi (Media Riset Akuntansi, Auditing & Informasi, 2016)
The objective of the empirical study is to examine and analyze the influence of Bonus Motivation, Tax Motivation, and Debt Motivation in Earning Management. The variables studied are bonus, tax, debt, firm size, and earning management. The sample of this study is the manufacture company that listed in Indonesia Stock Exchange in 2013 until 2015. The sample used in this study were 165 samples. The classical assumption used is normality test, multicollinearity, autocorrelation, and heteroscedasticity test. Hypothesis test used is the coefficient of determination (R ²), simultant test (F-test) and invidual test(t-test). The results of this study indicate that (1) Bonus Motivation has positive significant influence in earning management. (2) Tax Motivation has positive significant influence in earning management (3) Debt Motivation has positive significant influence in earning management.Keywords: Earning Management, Bonus, Income Tax, Debt to Assets Ratio, Firm Size.